Anti-aging organosilicone acrylate resin, and preparation method and application thereof
By using UV-based and oligosiloxane-copy acrylate resin in silicone leather, the problems of insufficient adhesion and mechanical properties of existing silicone leather are solved, and higher adhesion, friction resistance and simplified production processes are achieved.
Patent Information
- Application Number
- CN202411768100.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
AI Technical Summary
The existing silicone leather has low adhesion, friction fastness, and poor tear and fracture strength in the base cloth, and the production process is complicated and non-environmental solvents are required.
The acrylate resin is co-modified with UV-based and oligosiloxane, and the oligosiloxane acrylate is synthesized by esterification reaction, and copolymerized with other alkenyl monomers and UV absorbers to form a resin with improved adhesion and mechanical properties, which is used to prepare silicone leather.
It improves the adhesion, friction resistance and tear breaking strength of silicone leather, simplifies the production process, avoids the use of non-environmental solvents, and is suitable for automobiles, ships and other decorative uses.
Smart Images

Figure BDA0005169514990000031 
Figure BDA0005169514990000032 
Figure BDA0005169514990000141
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional resins, and specifically relates to a method for preparing an aging-resistant organic silicon-modified acrylate resin and application of the resin in the preparation of organic silicon leather. Background Art
[0002] In recent years, silicone leather, i.e. artificial leather made from addition silicone rubber, has been very popular in the market due to its weather resistance, aging resistance, high and low temperature resistance, good waterproof and antifouling properties, flame retardancy, and easy cleaning and care (see CN 117779479A, CN 115652651A, CN117487456A, CN 117801675A), and the surface can produce a dry or sheepskin-like oily feel after being treated with additives. It has become a research and development hotspot in the fields of silicone, leather and new materials in recent years. However, the good hydrophobicity of silicone materials also leads to the low adhesion of silicone leather made from silicone rubber on the surface of the base fabric, poor friction fastness, and poor tear and fracture strength, which urgently needs to be improved.
[0003] As for the production process, the silicone leather currently produced by addition silicone rubber often needs to be primed with acrylic resin or thermoplastic TPU on the surface of the base fabric, then coated with an intermediate layer, and finally coated with a surface layer, i.e., a three-step coating process (see CN 117779479A, CN 115652651A, CN 117487456A) to produce the finished silicone leather. Obviously, this process is relatively complicated, and part of the production process often requires the use of non-environmentally friendly solvents such as toluene.
[0004] As we all know, small molecule oligosiloxanes can have the hydrophobic, aging-resistant, flame-retardant and other properties of traditional silicone polymers, but they are compatible with aliphatic or aromatic organic resins without microscopic phase separation, turbidity and other phenomena. Based on this, introducing small molecule oligosiloxanes into an acrylic resin coating system with strong adhesion and good internal cohesion by chemical bonding means is expected to improve the defects of existing silicone leather (referred to as silicone leather), and is expected to give the target material surface properties and feel similar to silicone leather and good physical and mechanical strength and adhesion of acrylic resin coatings, so that the target silicone leather can be widely used in many fields such as interior decorative leather (such as seats and steering wheel leather) for automobiles, ships and yachts, sports shoe leather, luggage leather, interior wall decorative cloth, electronic product accessories such as sports bracelets, iPads and mobile phone jackets. Summary of the invention
[0005] In view of the defects of traditional silicone leather, such as poor mechanical strength, low adhesion to base fabric, poor friction fastness, need for acrylic resin or thermoplastic polyurethane TPU primer, and complex processing technology, the present invention discloses a method for preparing an aging-resistant silicone acrylate resin, i.e., a modified acrylate resin containing UV groups and oligosiloxane segments in its structure, and the application of the resin in modified silicone leather. To this end, the present invention adopts the following technical solutions:
[0006] A method for preparing an aging-resistant organic silicon acrylate resin comprises two steps: preparing a reactive organic silicon source monomer, namely, oligosiloxane acrylate, and synthesizing a UV-based and oligosiloxane co-modified acrylate resin.
[0007] (1) Preparation of reactive organosilicon source monomers - oligosiloxane acrylates
[0008] In a three-necked flask equipped with a thermometer, a reflux condenser and an electric stirrer, oligosiloxane (OS-OH) containing C-OH in its structure and unsaturated olefinic carboxylic acid (VC) are weighed in sequence according to the metering ratio, and the molar ratio of OS-OH to VC is controlled to be about 1:1.2-10, and the mixture is stirred and mixed; then, according to the total mass of OS-OH and VC, 0.1%-0.5% of hydroquinone inhibitor, 0.1%-0.2% of esterification catalyst and 0-100% of water extraction solvent S1 are added based on the total mass of OS-OH and VC, and the mixture is heated to 80-110° C. for esterification and water extraction reaction for 4-8 hours. After the reaction is completed, the solvent S1 is firstly distilled to recover, and the residual VC is then distilled off under reduced pressure, and the product is then successively treated with 2% Na 2 CO 3 The solution was washed with aqueous solution and deionized water for three times respectively, and then dried with anhydrous magnesium sulfate and filtered to obtain a colorless transparent to translucent liquid, which is oligosiloxane acrylate (OSA).
[0009] (2) Synthesis of UV- and oligosiloxane-modified acrylic resins
[0010] Weigh 5.0-30.0 parts of oligosiloxane acrylate (OSA), 46.0-90.0 parts of acrylate (AE), 0-10.0 parts of acrylonitrile (AN), 3.0-8.0 parts of hydroxyl olefin monomer (HA), 1-2.0 parts of other olefin functional monomers, and 1.0-4.0 parts of olefin ultraviolet absorber (AUV) by mass, stir and mix, and ultrasonically disperse to obtain a monomer mixture A; then, add 0.5%-1% of a free radical initiator by mass based on the total mass of A to obtain a monomer mixture B; divide B into two parts, (I) and (II), (I) is about 1 / 3-1 / 4 of the total mass of B, and (II) is about 2 / 3-3 / 4 of the total mass of B, and set aside.
[0011] Take (I) and the measured solvent S2, stir and heat to 75-85°C for 10-30 minutes, then add (II) dropwise at a uniform rate and allow it to drip completely within 2 hours, then keep warm and react for 2-4 hours to obtain a transparent to slightly turbid viscous liquid, which is a UV-based and oligosiloxane co-modified acrylate resin (OSPA) with a solid content of about 50%-60%.
[0012] The oligosiloxane acrylate has a structure as shown in formula (1) and / or (2), and is a (polyether) acrylate having a heptamethyltrisiloxane segment connected to one end of the molecule [see formula (1), referred to as heptamethyltrisiloxane (polyether) acrylate], or a (polyether) acrylate having a trimethylsilyl-terminated polydimethylsiloxane segment connected to one end of the molecule [see formula (2), referred to as polydimethylsiloxane (polyether) acrylate];
[0013]
[0014] In formula (1) and (2), the polyether group is a polyoxyethylene polyoxypropylene ether group, a, a 1 =0-3, b, b 1 =0-10, a+b=0-10, a 1 +b 1 =0-10; M, M′=H, CH 3 ; R=H or CH 3 ; n = 4-40.
[0015] The oligosiloxane acrylate can be prepared by the esterification and dehydration reaction of (polyether) oligosiloxane OS-OH [see formula (3)-(4)] containing C-OH at one end of the molecule and unsaturated olefinic carboxylic acid (VC) or can be directly ordered from relevant manufacturers;
[0016]
[0017] In formula (3)-(4), a, a 1 ,b,b 1 , the definition and value of n are the same as those in formulas (1)-(2).
[0018] The (polyether) oligosiloxane containing C-OH at one end of the molecule is selected from 3-hydroxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane with a=0 and b=0, 3-(hydroxyethyloxypropyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane with a=1 and b=0, and 3-(hydroxy-terminated polyoxyethylene polyoxypropylene propyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane with a=0-3 and b=0-10, or a 1 =0, b 1= 0, n = 4-40, one end of the molecule is hydroxypropyl and the other end is trimethylsilyl-terminated polydimethylsiloxane (referred to as single-terminated hydroxypropyl polydimethylsiloxane, the same below) (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] n Si(CH 3 ) 2 C 3 H 6 OH, a 1 =1, b 1 =0 single-end hydroxyethyloxypropyl polydimethylsiloxane (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] n Si(CH 3 ) 2 C 3 H 6 OC 2 H 4 OH, a 1 =0-3, b 1 = 0-10, n = 4-40 single-end hydroxyl-terminated polyoxyethylene polyoxypropylene propyl polydimethylsiloxane (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] n Si(CH 3 ) 2 C 3 H 6 (OC 2 H 4 ) a1 (OC 2 H 4 ) b1 One of OH.
[0019] The siloxane oligomers such as 3-hydroxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane, 3-hydroxyethyloxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane, 3-(hydroxy-terminated polyoxyethylene polyoxypropylene propyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane with a=0-3 and b=0-10 were commissioned by Shaanxi Andy Gill New Materials Co., Ltd. or Zhejiang Runhe New Materials Co., Ltd. to use 1,1,1 ,3,5,5,5-heptamethyltrisiloxane and allyl alcohol, or hydroxyethyl allyl ether, or a=0-3, b=0-10 hydroxyl-terminated polyoxyethylene polyoxypropylene allyl ether under the action of platinum catalyst by hydrosilylation addition reaction or customization; the single-terminated hydroxypropyl polydimethylsiloxane, single-terminated hydroxyethyloxypropyl polydimethylsiloxane, single-terminated hydroxyl-terminated polyoxyethylene polyoxypropylene propyl polydimethylsiloxane are synthesized or customized by single-terminated dimethyl hydrogen silicon-terminated polydimethylsiloxane [(CH 3 ) 3 SiO[(CH 3 ) 2 SiO] n Si(CH 3 ) 2 H] is synthesized by hydrosilylation addition reaction with allyl alcohol, or hydroxyethyl allyl ether, or hydroxyl-terminated polyoxyethylene polyoxypropylene allyl ether in the presence of platinum catalyst. The products available in the market are directly ordered from the relevant companies, while the products not sold in the market are commissioned to Zhejiang Runhe New Materials Co., Ltd. and others for processing and synthesis.
[0020] The unsaturated olefinic carboxylic acid is one of acrylic acid, methacrylic acid, 2-butenoic acid and 5-hexenoic acid; the esterification reaction catalyst is aluminum acetylacetonate or chromium acetylacetonate.
[0021] The solvent S1 is a small molecular aromatic hydrocarbon, cycloalkane or ester solvent with a low boiling point, and is selected from one of benzene, toluene, ethyl acetate, cyclohexane, methylcyclohexane and the like.
[0022] The acrylate is an aliphatic or alicyclic (meth) acrylate, such as an aliphatic acrylate C 1-18 Alkyl esters, aliphatic methacrylate C 1-18 Alkyl esters, containing C 5-10 Alicyclic hydrocarbon acrylates, etc., are selected from one or more mixtures of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, dodecanol (meth)acrylate, hexadecanol (meth)acrylate, butyl octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, isobornyl (meth)acrylate, etc.
[0023] The hydroxyethyl monomer (HA) is a compound containing C-hydroxyl and alkenyl in the molecular structure, and is selected from one of hydroxyethyl allyl ether, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, etc.;
[0024] The other alkenyl functional monomers are small molecular compounds containing both silane alkoxy groups and double bonds in the structure (also known as alkenyl alkoxy silanes), such as (meth)acryloxypropyl silane or vinyl silane, etc.; one of (meth)acryloxypropyl methyldimethoxysilane, (meth)acryloxypropyl trimethoxysilane, (meth)acryloxypropyl methyldiethoxysilane, (meth)acryloxypropyl triethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, methyl vinyl dimethoxysilane, methyl vinyl diethoxysilane, etc. is selected.
[0025] The alkenyl UV absorber is a compound containing a 2-hydroxybenzophenone derivative group and a double bond in its structure, and is selected from one of 4-propyleneoxy-2-hydroxybenzophenone (also known as 2-hydroxy-4-propyleneoxybenzophenone), 2-hydroxy-4-(methacryloyloxy)benzophenone, 4-(β-hydroxy-γ-allyloxy)propoxy-2-hydroxybenzophenone, etc.
[0026] The free radical initiator is an oil-soluble initiator, which is selected from one of benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), percarbonate and the like.
[0027] The solvent S2 is a solvent such as a small molecule aromatic hydrocarbon, ester, alcohol ether, alcohol ether ester, ketone, etc., and is selected from one or a mixture of 2-3 of benzene, toluene, propylene glycol dimethyl ether, propylene glycol diethyl ether, ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, propylene glycol methyl ether acetate, etc.
[0028] The aging-resistant silicone acrylate resin, i.e., UV-based and oligosiloxane co-modified acrylate resin, has as its main component a multi-component copolymer of oligosiloxane acrylate-co-acrylate-co-acrylonitrile-other olefinic functional monomers-co-olefinic UV absorbers, or a multi-component copolymer of oligosiloxane acrylate-co-acrylate-co-other olefinic functional monomers-co-olefinic UV absorbers.
[0029] The application of the anti-aging organic silicone acrylate resin is the application of UV-based and oligosiloxane co-modified acrylate resin in the preparation of organic silicone acrylate leather, including two steps of slurry preparation and silicone leather preparation:
[0030] (1) Preparation of leather slurry: Take 100.0 parts of aging-resistant silicone acrylate resin OSPA, 1.0-5.0 parts of oil-soluble color paste, 0.5-1.0 parts of BYK-ATU wetting and dispersing agent, and 5-10 parts of skin collagen fiber powder by mass, stir and mix, stir and disperse with a disperser at a speed of about 500-1000 r / m for 20-30 minutes, and vacuum degas to obtain leather slurry A;
[0031] Take another polyisocyanate curing agent, control the dosage so that the amount ratio of hydroxyl C-OH contained in OSPA of leather making slurry A to -NCO contained in the polyisocyanate curing agent is about 1:1-1.2, and then dilute it with a diluent solvent to a content of about 50% to obtain material B; then, stir and mix material A and material B according to the metering ratio, and then use a thickener to adjust it into a fluid with a viscosity of about 5000-20000mPa.s, which is the leather making slurry.
[0032] (2) Preparation of silicone acrylate leather: Lay a base fabric flat on the surface of a test bench, and evenly scrape the leather slurry on the surface of the base fabric with a wire rod or a scraper, and control the amount of slurry so that the coating thickness after drying is controlled to be about 150-300 μm, and then adhere it with a masking release paper, and then cure it at 80-120° C. for 20-30 minutes; then, remove the masking release paper, and then spray a layer of leather feel agent on the leather surface, and bake it in a drying room at 80-90° C. for 30-60 minutes. The resulting leather sample is the silicone acrylate leather prepared by the present invention.
[0033] The oil-soluble color paste is a solvent-based or oil-soluble resin general color paste produced by Clariant, Henan Wangong Environmental Protection Materials Co., Ltd., BASF and other companies, such as Colanyl Black N131-CN003, DF616 Permanent Red F5, DF618 Permanent Red F2, DF816 Standard Medium Yellow, Permanent Purple, etc.; the leather collagen fiber powder is a powdery substance obtained by crushing the scraps produced in the production process of natural leather such as pig skin, cowhide, sheepskin, etc., and is provided by Wenzhou Shuguang Leather Co., Ltd.
[0034] The polyisocyanate curing agent is a polyisocyanate containing 2-3 -NCO functional groups in the structure, a diisocyanate grafted with a polyether diol (-g-), or a diisocyanate grafted with a polyester diol (-g-), and is selected from N3390, N-75 produced by Bayer or Sikotron, polytetramethylene ether diol-g-di(isophorone diisocyanate) with an average molecular weight (Mn) of about 1000-2000, or polycaprolactone diol-g-di(isophorone diisocyanate) with an Mn of 1000-2000, etc.; the thickener is an associative nonionic polyurethane thickener 8W and similar products produced by Rohm & Haas.
[0035] The base fabric is a fabric used as a base material, and is selected from one of polyester non-woven fabric, polyurethane non-woven fabric, polyester or spandex or polyurethane microfiber fabric, etc.; the feel agent is a substance that can make the surface of leather or synthetic leather feel smooth or sheepskin-like comfortable and oily, such as the oil / water dual-purpose DC-Q2-3238, DC-57 feel agent produced by Dow Corning.
[0036] The application performance of the silicone acrylate leather is tested and evaluated by the following methods: Tensile strength and elongation at break: Tested with 1036PC universal testing machine in accordance with GB / T528-2009 standard. Leather surface hydrophobicity: expressed by the static contact angle (WCA) of a water droplet on the leather surface, using a JC-2000C1 static contact angle measuring instrument, with a water droplet size of 5 μL, and the value is the average of three different measured values; Aging resistance (1000h×85℃×RH85%): Tested with KK-SN-150 xenon lamp aging resistance test box in accordance with GB / T2423.24-1995 standard. Water vapor permeability: Tested with a water vapor permeability tester in accordance with GB / T12704.2-2009.
[0037] The beneficial effects of the present invention are as follows: the present invention utilizes the esterification reaction of (polyether) oligosiloxane containing C-OH at one end of the molecule and unsaturated olefinic carboxylic acid VC under the action of a catalyst and an inhibitor, firstly synthesizing an organosilicon source monomer containing a reactive double bond in its structure, namely, oligosiloxane acrylate (OSA); then, OSA is reacted with aliphatic or alicyclic acrylate, an olefinic ultraviolet absorber (AUV), a hydroxyl olefin monomer, and other olefinic functional monomers (such as acryloxypropyl alkoxy) that can produce a crosslinking reaction in the subsequent application process. The invention relates to a method for preparing a synthetic leather made of organic silicon acrylic resin. The method comprises the following steps: first, using an organic silicon acrylic resin as a base material, and then using an organic silicon acrylic resin as a base material to carry out free radical multi-polymerization, thereby synthesizing a polyacrylate resin OSPA having functional chain segments such as oligosiloxane segments and 2-hydroxybenzophenone derivative UV absorption groups in the structure; then, using OSPA as a film-forming substance, using polyisocyanate as a curing component, and using natural leather collagen fiber powder as a moisture-absorbing and breathable added component to compound the components into a leather-making slurry. When applied, the slurry is applied to the surface of the base cloth, and then heated and cured and a hand-feel layer is sprayed, thereby preparing a kind of organic silicon acrylic resin synthetic leather. The application shows that the synthetic leather prepared with the resin of the invention not only has an oily feel similar to that of leather and organic silicon leather, good water repellency, dustproofness, air permeability, and aging resistance, but also has better mechanical properties such as friction resistance. Obviously, this provides an innovative idea for industrial improvement of the shortcomings of existing organic silicon leather. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to the embodiments.
[0039] Example 1
[0040] (1) Synthesis of oligosiloxane acrylate - 3-(acryloyloxypolyoxypropylenepropyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane
[0041] In a reactor equipped with a thermometer, a reflux condenser and an electric stirrer, 3-(hydroxy-terminated polyoxypropylene propyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH 3 )C 3 H 6 (OC 3 H 6 ) 3 The molar ratio of OH (HMTS-OH-1, commissioned by Shaanxi Andy Gill New Materials Co., Ltd. for processing and synthesis, the same below): acrylic acid (AA) is about 1:2. 0.1 mol (about 45.45 g) of HMTS-OH-1 and 0.2 mol (about 14.41 g) of AA are weighed in sequence, and then 0.2% (about 0.12 g) of hydroquinone inhibitor, 0.1% (about 0.06 g) of acetylacetonate aluminum catalyst and 50% (about 29.93 g) of cyclohexane solvent are added based on the total mass of HMTS-OH-1 and AA. The mixture is stirred and mixed, and the mixture is heated to 90°C for reflux and water extraction reaction for 4 hours. After the reaction is completed, the cyclohexane solvent is first recovered by atmospheric distillation, and then the cyclohexane solvent is recovered by atmospheric distillation at a pressure of P 表 =0.085MPa under reduced pressure to evaporate the residual AA, and then the product was successively treated with a mass concentration of about 2% Na 2 CO 3 The mixture was washed with water and deionized water for three times to remove the residual catalyst and inhibitor in the system, and then 5.20 g of anhydrous magnesium sulfate was added to dry for 2 hours and filtered to obtain a colorless transparent liquid, i.e., a low molecular weight siloxane acrylate having a structure as shown in formula (1) with a=0, b=3, M=H, and R=H, namely, 3-(acryloyloxypolyoxypropylenepropyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH 3 )C 3 H 6 (OC 3 H 6 ) 3 OCOCH=CH 2 , denoted as OSA-1.
[0042] (2) Preparation of UV- and oligosiloxane-modified acrylate resin OSPA-1
[0043] In a four-necked reaction flask equipped with a thermometer, a reflux condenser and an electric stirrer, 30.0 g of OSA-1, 35.0 g of butyl acrylate, 5.0 g of cyclohexyl methacrylate, 18.0 g of methyl methacrylate (MMA), 5.0 g of acrylonitrile (AN), 5.0 g of hydroxypropyl acrylate (HPAA), 1.0 g of methacryloyloxypropylmethyldimethoxysilane (KH-571) and 1.0 g of 4-allyloxy-2-hydroxybenzophenone were weighed, stirred and mixed, and ultrasonically dispersed for 10 min using an ultrasonic cleaner with a power of 1000 W to obtain a total of about 100.0 g of monomer mixture A, and then 1% of the mass of A, about 1.0 g of BPO, was added to obtain a monomer mixture B. B was divided into two parts, (I) and (II), of which (I) accounted for about 1 / 3 of the mass of B and (II) accounted for about 2 / 3 of the mass of B, and were set aside.
[0044] Take (I) and 66.67g of butyl acetate (BA), stir and heat to 80°C to react for 30min, then add (II) dropwise and allow it to drip completely within 2h, then continue to keep warm at 80°C for 4h, and the reaction is completed to obtain a total of about 166.67g of a transparent viscous liquid, i.e., a modified acrylic resin having a main chain structure with 2-hydroxybenzophenone group and heptamethyltrisiloxanepropyl polyoxypropylene ether group suspended therein - OSA-1-co-butyl acrylate-co-cyclohexyl methacrylate-co-methyl methacrylate-co-acrylonitrile-co-hydroxypropyl acrylate-co-methacryloxypropyl methyldimethoxysilane-co-4-allyloxy-2-hydroxybenzophenone copolymer, with a solid content of about 60wt%, recorded as OSPA-1.
[0045] Example 2
[0046] (1) Synthesis of oligosiloxane acrylate - single-end trimethylsilyl polydimethylsiloxane propyl polyoxypropylene acrylate
[0047] In a reactor equipped with a thermometer, a reflux condenser and an electric stirrer, an oligosiloxane (OS-OH) containing C-OH in the structure of formula (4) is added. 1 =0, b 1 =5, n=38 single-end hydroxyl-terminated polyoxypropylene propyl polydimethylsiloxane (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] 38 Si(CH 3 ) 2 C 3 H 6 (OC 3 H 6 ) 5The molar ratio of OH (MPSPE-OH-1): acrylic acid (AA) is about 1:10. 0.01 mol (about 33.09 g) of MPSPE-OH-1 and 0.1 mol (about 7.21 g) of AA are weighed in sequence, and then 0.5% (about 0.20 g) of hydroquinone inhibitor, 0.2% (about 0.08 g) of aluminum acetylacetonate catalyst and 50%, about 20.15 g of methylcyclohexane are added based on the total mass of MPSPE-OH-1 and AA. The mixture is stirred and heated to 110°C for reflux and water extraction reaction for 6 hours. After the reaction is completed, the methylcyclohexane solvent is recovered by atmospheric distillation and then heated to a pressure of P 表 =0.09MPa under reduced pressure to evaporate the residual AA, and then the product was successively treated with about 2% Na 2 CO 3 The mixture was washed with water and deionized water for three times to remove the residual catalyst and inhibitor in the system, and then 5.0% anhydrous magnesium sulfate was added to dry for 2 hours, and filtered to obtain a colorless, slightly viscous, transparent liquid, which has the structure shown in formula (2). 1 =0, b 1 =5, n=38, M'=H, R=H, single-end trimethylsilyl-terminated polydimethylsiloxane propyl polyoxypropylene acrylate - (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] 38 Si(CH 3 ) 2 C 3 H 6 (OC 3 H 6 ) 5 OCOCH=CH 2 , denoted as OSA-2.
[0048] (2) Preparation of UV- and oligosiloxane-modified acrylate resin OSPA-2
[0049] In a four-necked reaction flask equipped with a thermometer, a reflux condenser and an electric stirrer, 5.0 g of OSA-2, 30.0 g of butyl acrylate, 10.0 g of isooctyl acrylate, 12.0 g of cyclohexyl methacrylate, 19.0 g of methyl methacrylate, 10.0 g of acrylonitrile, 8.0 g of hydroxyethyl acrylate (HEAA), 2.0 g of vinyl triethoxysilane and 4.0 g of 2-hydroxy-4-(methacryloyloxy)benzophenone were weighed, stirred and mixed, and ultrasonically dispersed for 20 minutes to obtain a total of about 100.0 g of monomer mixture A. Then, 0.5% (about 0.5 g) of BPO was added based on the total mass of the polymerizable monomers contained in A to obtain a monomer mixture B. B was divided into two parts, (I) and (II), of which (I) accounted for about 1 / 4 of the mass of B and (II) accounted for about 3 / 4 of the mass of B, and used for later use.
[0050] Take (I) and 100.0g of propylene glycol dimethyl ether (DMP), stir and heat to 80°C for reaction for 10min, then add (II) dropwise and allow it to drip completely within 2h, then continue to keep warm at 80°C for reaction for 2h. After the reaction is completed, a total of about 200.0g of transparent viscous liquid is obtained, i.e., a modified polyacrylate resin having a main chain structure with 2-hydroxybenzophenone group and trimethylsilyl-terminated polydimethylsiloxane propyl polyoxypropylene segment suspended therein - OSA-2-co-butyl acrylate-co-isooctyl acrylate-co-cyclohexyl methacrylate-co-methyl methacrylate-co-acrylonitrile-co-hydroxyethyl acrylate-co-vinyltriethoxysilane-co-2-hydroxy-4-methacryloyloxybenzophenone copolymer, with a solid content of about 50wt%, recorded as OSPA-2.
[0051] Example 3
[0052] (1) Synthesis of oligosiloxane acrylate: 3-(methacryloyloxyethyleneoxypropyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane
[0053] In a reactor equipped with a thermometer, a reflux condenser and an electric stirrer, 3-(hydroxyethyloxypropyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH 3 )C 3 H 6 OC 2 H 4The molar ratio of OH (HMTS-OH-2, Shaanxi Andy Gill New Materials Co., Ltd.): methacrylic acid (MAA) is about 1:1.5. 0.1 mol (about 32.45 g) of HMTS-OH-2 and 0.15 mol (about 12.31 g) of MAA are weighed in sequence, and then 0.3% (about 0.13 g) of hydroquinone inhibitor, 0.15% (about 0.067 g) of aluminum acetylacetonate catalyst and 67%, about 30.0 g of benzene are added based on the total mass of HMTS-OH-2 and MAA. The mixture is stirred and heated to 90°C for reflux and water extraction reaction for 4 hours. After the reaction is completed, the benzene solvent is recovered by atmospheric distillation and then heated to a pressure of P 表 = 0.09MPa under reduced pressure to evaporate the residual MAA, and then the product was successively treated with a mass concentration of about 2% Na 2 CO 3 The mixture was washed with water and deionized water for three times to remove the residual catalyst and inhibitor, and then 6.0 g of anhydrous magnesium sulfate was added to dry for 2 h, and filtered to obtain a colorless transparent liquid, i.e., an oligosiloxane acrylate having a structure as shown in formula (1), a=0, b=1, M=Me, and R=H, namely, 3-(methacryloyloxyethyleneoxypropyl)heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH 3 )C 3 H 6 OC 2 H 4 OCCMe=CH 2 , denoted as OSA-3.
[0054] (2) Preparation of UV- and oligosiloxane-modified acrylate resin OSPA-3
[0055] In a four-necked reaction flask equipped with a thermometer, a reflux condenser and an electric stirrer, 20.0 g of OSA-3, 45.0 g of butyl acrylate, 10.0 g of isobornyl methacrylate, 16.0 g of methyl methacrylate (MMA), 6.0 g of hydroxypropyl acrylate (HPAA), 1.0 g of methacryloyloxypropyltrimethoxysilane (KH-570) and 2.0 g of 4-allyloxy-2-hydroxybenzophenone were weighed and mixed, and ultrasonically dispersed for 10 min using an ultrasonic cleaner with a power of 1000 W to obtain a total of about 100.0 g of monomer mixture A, and then 0.6% of the mass of A, about 0.6 g of benzoyl peroxide (BPO), was added to obtain a monomer mixture B. B was divided into two parts, (I) and (II), of which (I) accounted for about 1 / 4 of the mass of B and (II) accounted for about 3 / 4 of the mass of B, and were set aside.
[0056] Take (I) and 66.67g of ethyl acetate (EA), stir and heat to 80°C to react for 20min, then add (II) dropwise and allow it to drip completely within 2h, then continue to keep warm at 80°C for 4h. After the reaction is completed, a total of 166.67g of a transparent viscous liquid is obtained, i.e., a modified acrylic resin having a main chain structure with 2-hydroxybenzophenone groups and heptamethyltrisiloxane segments suspended therein - OSA-3-co-butyl acrylate-co-isobornyl methacrylate-co-methyl methacrylate-co-hydroxypropyl acrylate-co-methacryloxypropyltrimethoxysilane-co-4-allyloxy-2-hydroxybenzophenone copolymer, with a solid content of about 60wt%, recorded as OSPA-3.
[0057] Example 4
[0058] (1) Synthesis of oligosiloxane acrylate - 3-acryloxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane
[0059] In a reactor equipped with a thermometer, a reflux condenser and an electric stirrer, 3-hydroxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH 3 )C 3 H 6 The molar ratio of OH (HMTS-OH-3): acrylic acid (AA) is about 1:1.2. 0.1 mol (about 28.05 g) of HMTS-OH-3 and 0.12 mol (about 8.65 g) of AA are weighed in sequence. Then, according to the total mass of HMTS-OH-3 and AA, 0.14% (about 0.05 g) of hydroquinone inhibitor, 0.1% (about 0.04 g) of acetylacetonate aluminum catalyst and 70% (about 25.69 g) of cyclohexane are added, based on the mass of HMTS-OH-3 + AA. The mixture is stirred and heated to 90°C for reflux and water extraction reaction for 5 hours. After the reaction is completed, the cyclohexane solvent is first recovered by atmospheric distillation, and then the mixture is heated to 90°C for reflux and water extraction reaction for 5 hours. 表 =0.085MPa under reduced pressure to evaporate the residual AA, and then the product was successively treated with a mass concentration of about 2% Na 2 CO 3 The mixture was washed with water and deionized water for three times to remove the residual catalyst and inhibitor, and then 5.0 g of anhydrous magnesium sulfate was added to dry for 2 h, and filtered to obtain a colorless transparent liquid, i.e., 3-acryloxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH3 )C 3 H 6 OCOCH=CH 2 , denoted as OSA-4.
[0060] (2) Preparation of UV- and oligosiloxane-modified acrylate resin OSPA-4
[0061] In a four-necked reaction flask equipped with a thermometer, a reflux condenser and an electric stirrer, 20.0 g of OSA-4, 15.0 g of ethyl acrylate, 25.0 g of butyl acrylate, 5.0 g of isooctyl methacrylate, 25.0 g of methyl methacrylate, 5.0 g of HPAA, 1.0 g of KH-570 and 4.0 g of 4-allyloxy-2-hydroxybenzophenone were weighed and ultrasonically dispersed for 10 min using an ultrasonic cleaner with a power of 1000 W to obtain a total of about 100.0 g of monomer mixture A, and then 0.8% of the mass of A, about 0.8 g of azobisisobutyronitrile (AIBN), was added to obtain a monomer mixture B. B was divided into two parts, (I) and (II), of which (I) accounted for about 1 / 4 of the mass of B and (II) accounted for about 3 / 4 of the mass of B, and were set aside.
[0062] Take (I) and 100.0g of ethyl acetate, stir and heat to 75°C for reaction for 25min, then add (II) dropwise and allow it to drip completely within 2h, then continue to keep warm at 80°C for 2h, and the reaction is completed to obtain a total of about 200.0g of a transparent viscous liquid, i.e., a modified acrylic resin having a 2-hydroxybenzophenone derivative group and a heptamethyltrisiloxane oligosiloxane segment suspended in the main chain - OSA-4-co-ethyl acrylate-co-butyl acrylate-co-isooctyl methacrylate-co-methyl methacrylate-co-hydroxypropyl acrylate-co-methacryloxypropyltrimethoxysilane-co-4-allyloxy-2-hydroxybenzophenone copolymer, i.e., a solid content of about 50wt%, recorded as OSPA-4.
[0063] Example 5
[0064] (1) Oligomeric siloxane acrylate is used to carry out subsequent synthesis reaction using commercially available imported single-end acryloxypropyl polydimethylsiloxane with a viscosity of about 60 mm / s, a functional group equivalent of 4600, and a grade of X-22-174DX.
[0065] (2) Preparation of UV- and oligosiloxane-modified acrylate resin OSPA-5
[0066] In a four-necked reaction flask equipped with a thermometer, a reflux condenser and an electric stirrer, 6.0 g of single-end acyloxypropyl polydimethylsiloxane X-22-174DX, 44.0 g of butyl acrylate, 15.0 g of cyclohexyl methacrylate, 20.0 g of methyl methacrylate, 5.0 g of acrylonitrile, 5.0 g of hydroxyethyl acrylate (HEAA), 1.0 g of 3-acryloxypropylmethyldimethoxysilane KH-572 and 4.0 g of 2-hydroxy-4-(methacryloyloxy)benzophenone were weighed and mixed, and ultrasonically dispersed for 20 min using an ultrasonic cleaner with a power of 1000 W to obtain a total of about 100.0 g of monomer mixture A, and then 0.6% (about 0.6 g) of BPO was added based on the total mass of A, and stirred to obtain a monomer mixture B. Divide B into two parts, (I) and (II), of which (I) accounts for about 1 / 3 of the mass of B and (II) accounts for about 2 / 3 of the mass of B, and keep them in reserve.
[0067] Take (I) and 66.67g of DMP, stir and heat to 80°C to react for 20min, then add (II) dropwise and allow it to drip completely within 2h, then continue to keep warm at 80°C for 3h, and the reaction is completed to obtain a total of 166.67g of a transparent viscous liquid, i.e., a modified acrylic resin having a main chain structure with 2-hydroxybenzophenone derivative groups and polydimethylsiloxane segments suspended therein - a single-terminal acyloxypropyl polydimethylsiloxane-co-butyl acrylate-co-cyclohexyl methacrylate-co-methyl methacrylate-co-acrylonitrile-co-hydroxyethyl acrylate-co-acryloxypropyl methyldimethoxysilane-co-2-hydroxy-4-methacryloxybenzophenone copolymer, with a solid content of about 60wt%, recorded as OSPA-5.
[0068] Example 6
[0069] Without adding OSA-1, 35.0 g of butyl acrylate, 5.0 g of cyclohexyl methacrylate, 18.0 g of methyl methacrylate, 5.0 g of acrylonitrile, 5.0 g of hydroxypropyl acrylate, 1.0 g of methacryloyloxypropylmethyldimethoxysilane, and 1.0 g of 4-allyloxy-2-hydroxybenzophenone were subjected to free radical copolymerization in 46.69 g of butyl acetate (BA) at 80° C. for 4 h in the same manner as in Example 1. The resulting acrylic resin, a copolymer of butyl acrylate-co-cyclohexyl methacrylate-co-methyl methacrylate-co-acrylonitrile-co-hydroxypropyl acrylate-co-methacryloyloxypropylmethyldimethoxysilane-co-allyloxy-2-hydroxybenzophenone, was used as reference PA-1 of the present invention.
[0070] Example 7
[0071] Methoxy-terminated polyoxypropylene ether CH 3(OC 3 H 6 ) 3 Methoxy-terminated polyoxypropylene acrylate CH 3 (OC 3 H 6 ) 3 OCOCH=CH 2 Instead of 3-(acryloyloxypolyoxypropylenepropyl)-1,1,1,3,5,5,5-heptamethyltrisiloxane [(CH 3 ) 3 SiO] 2 Si(CH 3 )C 3 H 6 (OC 3 H 6 ) 3 OCOCH=CH 2 , the other steps are the same as step (2) of Example 1, and the free radical copolymerization reaction of monomers such as acrylate is carried out. The obtained acrylate copolymer resin, a copolymer of methoxy-terminated polyoxypropylene acrylate-co-butyl acrylate-co-cyclohexyl methacrylate-co-methyl methacrylate-co-acrylonitrile-co-hydroxypropyl acrylate-co-methacryloxypropylmethyldimethoxysilane-co-4-allyloxy-2-hydroxybenzophenone, is used as the reference PA-2 of the present invention.
[0072] Take OSPA-1 to OSPA-5 prepared in Examples 1-7 and reference PA-1 and PA-2, dilute with ethyl acetate to a solid content of 50%, prepare leather slurry and use it in the preparation of silicone acrylate leather:
[0073] (1) Preparation of leather slurry: 60.0 g of OSPA-1 to OSPA-5 or reference PA-1 or PA-2 with a solid content of about 50 wt%, 1.0 g of universal DF616 permanent red F5 color paste (Zhengzhou Shichuang Chemical Products Sales Co., Ltd.), 0.5 g of BYK-ATU dispersant, and 10.0 g of skin collagen fiber powder are taken, and stirred and dispersed for 30 min using a disperser with a speed of about 500-1000 r / m, and then 1.0 g of non-ionic associative 8W thickener (Rohm & Haas Company) is added to make a paste, and vacuum degassing is performed to obtain slurry material A; then, polyisocyanate curing agent N-3390 is weighed according to the molar ratio of hydroxyl group to -NCO contained in material A OSPA of about 1:1.2, and diluted with ethyl acetate to a solid content of 50%, and then stirred and mixed with material A to obtain leather slurry.
[0074] (2) Preparation of silicone acrylate leather: A polyester microfiber leather base fabric (Changshu Jinda Nonwoven Products Co., Ltd.) or a release paper was laid flat and fixed on a test bench, and the above leather slurry was evenly coated on the surface of the base fabric or the release paper using an RDS-70 wire rod. The amount of slurry was controlled so that the coating thickness after drying was about 160 μm. A layer of masking release paper was then attached, and then cured at 80-120° C. for 30 min. The release paper was then removed, and a 0.5% ethanol solution of DC-Q2-3238 leather feel agent (Dow Corning, USA) was sprayed on the surface of the synthetic leather, and dried at 80° C. for 30 min. The leather sample obtained was the silicone acrylate leather (OSPA) of the present invention, and the following performance tests were performed:
[0075] Tensile strength and elongation at break: refer to GB / T528-2009 standard, use dumbbell-shaped I-type test specimens as test specimens and test them using a universal testing machine. Water absorption: take OSPA leather or reference, cut it into 1×1cm 2 The sample was weighed and immersed in water for 12 hours. It was taken out and the surface moisture of the leather was washed with filter paper. The sample was weighed again. The water absorption of the synthetic leather before and after immersion was calculated and the water absorption rate was calculated. The hydrophobicity of the leather surface was measured by the static contact angle (θ H2O ) indicated by JC-2000C1 static contact angle measuring instrument, water drop size is 5μL; aging resistance (1000h×85℃×RH85%): measured by KK-SN-150 xenon lamp aging test box in accordance with GB / T2423.24-1995 standard. Air permeability: measured by TQ-A digital leather air permeability tester in accordance with GB / T 4689.22-1996 leather air permeability test method; friction fastness: tested by friction tester.
[0076] In addition, commercially available hydrogen-containing silicone oil PHMS (Tangshan Sanyou Silicon Industry Co., Ltd.) with a Si-H content of about 0.18% and terminal vinyl silicone oil Bis-500 (Shanghai Jiancheng Silicone Co., Ltd.) with a vinyl (Vi) content of about 0.3wt% were taken and stirred and mixed at a Si-H: Vi molar ratio of about 1:1, and then 25g of PHMS and VPS silicone rubber mixture, 1 drop of complex platinum catalyst KP22, 1.0g of universal DF616 permanent red F5 color paste, 0.5g BYK-ATU dispersant, 10.0g of leather collagen fiber powder, and an appropriate amount of toluene solvent were added, and stirred and dispersed for 30min with a disperser at a speed of about 1000r / m, and vacuumed and degassed to obtain silicone rubber slurry, and then the silicone rubber slurry was evenly coated on the surface of polyester microfiber cloth or release paper, and cured at 110°C for 30min. The obtained silicone leather sample was also used as a reference of the present invention, and the performance test was carried out in the same way; all test results are shown in Table 1.
[0077] Table 1 OSPA silicone acrylate synthetic leather performance test results
[0078]
[0079] *1000h×85℃×85%; **Addition type silicone rubber, without adding fumed silica reinforcing agent
[0080] It should be understood that the examples are used to explain the embodiments of the present invention, and the protection scope of the present invention is not limited by the examples within the scope of the subject matter of the present invention.
Claims
1. A method for preparing an aging-resistant silicone acrylate resin, characterized in that: The oligosiloxane acrylate is subjected to a multi-radical copolymerization reaction with a base acrylate, a hydroxyl vinyl monomer, an alkenyl alkoxy silane, and an alkenyl ultraviolet absorber to obtain an aging-resistant silicone acrylate resin; or the oligosiloxane acrylate is subjected to a multi-radical copolymerization reaction with a base acrylate, acrylonitrile, a hydroxyl vinyl monomer, an alkenyl alkoxy silane, and an alkenyl ultraviolet absorber to obtain an aging-resistant silicone acrylate resin; The oligosiloxane acrylate has a structure as shown in formula (I) or formula (II): In the formula, a, a1 = 0-3, b, b1 = 0-10, a+b = 0-10, a1+b1 = 0-10; M, M′ = H or CH3; R = H or CH3; n = 4-40; The matrix acrylate is aliphatic acrylate or alicyclic acrylate; The hydroxy olefin monomer is a reactive monomer containing a C-hydroxyl group and an olefin group; The alkenyl alkoxy silane is a reactive silane containing an acryloxy group or a reactive silane containing an alkenyl group and an alkoxy group; The alkenyl ultraviolet absorber is a reactant containing a 2-hydroxybenzophenone derivative ultraviolet absorption group and an alkenyl group.
2. The method according to claim 1, characterized in that The oligosiloxane acrylate is obtained by esterification reaction of C-hydroxyl-containing oligosiloxane with alkenyl carboxylic acid; The C-hydroxyl-containing oligosiloxane has a structure as shown in formula (III) and / or formula (IV): In the formula, a, a1=0-3, b, b1=0-10, a+b=0-10, a1+b1=0-10; n=4-40.
3. The method according to claim 2, characterized in that The molar ratio of C-hydroxyl-containing oligosiloxane to alkenyl carboxylic acid is 1:1.2-10, the reaction temperature is 80-110°C, the reaction time is 4-6h, the catalyst is aluminum acetylacetonate, and the inhibitor is hydroquinone; The alkenyl carboxylic acid is one or more of acrylic acid, methacrylic acid, 2-butenoic acid, and 5-hexenoic acid.
4. The method according to claim 2, characterized in that: The C-hydroxyl-containing oligosiloxane is one or more of 3-hydroxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane, 3-hydroxyethyloxypropyl-1,1,1,3,5,5,5-heptamethyltrisiloxane, 3-hydroxy-terminated polyoxyethylene polyoxypropylene propyl-1,1,1,3,5,5,5-heptamethyltrisiloxane with a=0-3 and b=0-10, single-end hydroxypropyl polydimethylsiloxane with a1=0, b1=0 and n=4-40, single-end hydroxyethyloxypropyl polydimethylsiloxane with a1=1, b1=0 and n=4-40, and single-end hydroxyethyloxypropyl polydimethylsiloxane with a1=0-3, b1=0-10 and n=4-40.
5. The method according to claim 1, characterized in that The matrix acrylate is one or more of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, dodecanol (meth)acrylate, hexadecanol (meth)acrylate, butyl octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; The hydroxyethyl monomer is one or more of hydroxyethyl allyl ether, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate; The alkenyl alkoxysilane is one or more of methacryloxypropyltrialkoxysilane, acryloxypropyltrialkoxysilane, methacryloxypropylmethyldialkoxysilane, acryloxypropylmethyldialkoxysilane, vinyltrialkoxysilane, and vinylmethyldialkoxysilane, and the alkoxy group is methoxy or ethoxy; The alkenyl ultraviolet absorber is one or more of 4-propyleneoxy-2-hydroxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, and 4-β-hydroxy-γ-allyloxypropoxy-2-hydroxybenzophenone.
6. The method according to claim 1, characterized in that The steps include: Weigh 5-30 parts of oligosiloxane acrylate, 46-90 parts of matrix acrylate, 0-10 parts of acrylonitrile, 3-8 parts of hydroxyl vinyl monomer, 1-2 parts of alkenyl alkoxysilane, and 1-4 parts of alkenyl ultraviolet absorber by mass, and mix them by ultrasonic dispersion to obtain a monomer mixture A; then add 0.5%-1.0% of the total mass of free radical initiator according to the mass of A to obtain a monomer mixture B; divide the monomer mixture B into two parts, B1 and B2, for later use; Take B1 and solvent, stir and heat to 75-85℃ for reaction for 10-30min, then add B2 dropwise and make sure it is added completely within 2h, keep warm and react for 2-4h to obtain aging-resistant silicone acrylate resin.
7. Aging-resistant organosilicon acrylate resin prepared by the method according to any one of claims 1 to 6.
8. Use of the aging-resistant organosilicon acrylate resin according to claim 7 in the preparation of organosilicon-modified acrylate synthetic leather.
9. The use according to claim 8, characterized in that: The steps include: 1) Preparation of leather slurry: by weight, take 100 parts of the aging-resistant silicone acrylate resin according to claim 7, 0.5-5 parts of oil-soluble color paste, 0.5-1 parts of BYK-ATU wetting and dispersing agent, 5-10 parts of skin collagen fiber powder, stir and mix, then add polyisocyanate curing agent, and adjust to a paste with thickener to obtain leather slurry; 2) Preparation of silicone acrylate synthetic leather: Take a base fabric, evenly apply the leather-making slurry on the surface of the base fabric, cure it at 80-120°C for 20-30min, spray a leather feel agent, and obtain silicone acrylate synthetic leather.
10. The use according to claim 9, characterized in that: The polyisocyanate curing agent is one or more of polyisocyanate containing 2-3 -NCO functional groups, polyether diol diisocyanate, polyester diol diisocyanate; The leather collagen fiber powder is a powder obtained by crushing natural leather scraps; The thickener is an associative nonionic polyurethane thickener 8W; The hand feeling agent is one or more of DC-Q2-3238 and DC-57; The base fabric is one of polyester non-woven fabric, polyurethane non-woven fabric, polyester microfiber fabric, nylon microfiber fabric or polyurethane microfiber fabric.